Promosi Kesehatan dalam Meningkatkan Pengetahuan, Sikap dan Perilaku Deteksi Dini Kanker Serviks pada Ibu-Ibu Anggota Pengajian - Ismarwati I.M. Sunarsih Sutaryo, Rendra Widyatama (Berita Kedokteran Masyarakat (BKM), 2011)
Health Promotion in Improving Knowledge, Attitude and Behavior on Early Detection of Cervical Cancer in Women MemberBackground: As many as 80%-90% of cervical cancers tend to occur in women aged 30-55 years. Most cervical cancer are detected already in a late stage. Servical cancer prevention efforts can be done through health promotion using interactive discussions and audio visual media aid to promote an individual early detection efforts by pap smear or visual inspection with acetic acid (VIA).Objective: To determine the effect of health promotion through the media of audio-visual aid and interactive discussion in improving knowledge, attitude and behavior of As-Sakinah Recitation member in Banguntapan Subdistrict on an effort of cervical cancer early detection.Methods: Qualitative research used action research approached. The sampling method applied by the purposivesampling with women’s criteria are As Sakinah recitation members who had never undergone a hysterectomy (surgical removal of the uterus), had married (ever married), willing to become as an informant. Data was collected by in-depth interview to reveal in detail the opinions of someone about cervical cancer and its early detection efforts. Data analysis used was open code program.Results: Health promotion using the audio-visual film and interactive discussions on the forum are limited and have personal ties among the participants, effective for increasing knowledge and positive attitudes towards cervical cancer and early detection. The behavior of mothers early detection of cervical cancer by an individual (alone) is not ready (unfavorable) because they feel shame and no sense of worry about the results of early detection if it turns out the results tested positive. They are willing to (favorable) early detection collectively. Efforts to maintain reproductive health is done by avoiding risk factors pray and worship (prayers).Conclusions: The audio visual media and also interactive discussion in health promotion could improve knowledge and positive attitude towards early detection of cervical cancer on the women’s member of As Sakinah recitation. Knowledge and positive attitude toward the urgency of cervical cancer early detection could not guarantee the occurring of early detection behavior. The member of As Sakinah recitation was had no early detection personally because shy and afraid with the result of early detection. They are willing to do a joint (collective) and facilitated in the neighborhood.Keywords: health promotion, audio visual and interactive discussions, early detection of cervical cancer